September 11 : Every Now and Then - Book 3 - Kingsbury, Karen (Detroit : Thorndike Press, 2008)
Still grieving his father's death in the twin towers on September 11, sheriff's deputy Alex Brady concentrates on fighting crime in Los Angeles, until the worst fire season in California history sends him in pursuit of environmental terrorists, risking his life and his soul in the process.
Keywords: Large print books; Christian fiction